التحليل اللّساني النصي للمنجز اللّغوي الإبداعي في الشعر الجزائري المعاصر قصيدة "أسرى الكلام" لفاتح علّاق أنموذجا (El-Wahat Journal for Research and Studies, 2021)
This Research Highlights The Efforts Of Modern Linguistic Studies Represented In Text-Linguistics Which Examine The Mechanisms That Are Based On The Construction Of Texts That Represents A Model Of Human Communication. The Study Reveals Two Important Concepts: (Cohesion & Coherence), That Are Required To Confirm The Textuality Of The Text.  I.E. To Seek The Linguistic And Non-Linguistic Means That Are Combined To Form The Whole Text And The Cohesion Of Parts.In Order To Give A Clear Idea Of These Terms, We Try To Apply Them To A Contemporary Text Of Poetry Of An Algerian Poet Who Is Fateh ALLAG. Key Words- (Text Linguistics, Cohesion, Coherence, Context, Consistency).